Sintesis dan Karakterisasi Komposit Mn-N-TiO2/Bentonit untuk Degradasi Polutan Organik: Synthesis and Characterization of Mn-N-TiO2/Bentonite Composite for Organic Pollutants Degradation - Ruslan; Prismawiryanti; Sumarni, Ni Ketut; Ridhay, Ahmad; Riski, Mutiara Zalfa; Nurhalisa, Sitti; Marsela, Anggi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
Research has been conducted on the synthesis and characterization of Mn-N-TiO2/Bentonite composites for the degradation of organic pollutants. This study aims to synthesize the Mn-N-TiO2/Bentonite composite as a catalyst in degrading congo red in visible light and to determine the effect of irradiation time on the effectiveness of photodegradation of congo red catalyzed Mn-N-TiO2/Bentonite. The synthesis of the Mn-N-TiO2/Bentonite composite was carried out using the sol-gel method. Characterization was carried out with UV-Vis DRS, XRD, FTIR, and SEM-EDX. A photocatalytic activity test on Congo red degradation was carried out using ultraviolet and visible lamps. The results of the characterization of the Mn-N-TiO2/Bentonite configuration show that the band gap energy of Mn-N- TiO2/Bentonite with a variation of 5 g has a band gap energy of 2.14 eV with anatase crystal form. In the IR spectrum, there is a shift in wave number from 1634.49 to 1433.11cm-1, there is the vibration of the NO bond, absorption below 1000 cm-1 indicates the presence of Mn-O bonds, and absorption at wave number 1049.28 cm-1 indicates the presence of ions. manganese metal trapped in the TiO2 matrix. This spectrum indicated the presence of manganese and nitrogen. These results were confirmed by the EDX instrument, which showed the presence of 0.60% Mn and 0.04% N. SEM results show that particles that are still agglomerated and have a large size, which is influenced by water vapor in the TiO2 crystal structure. The results showed that the photodegradation activity increased significantly up to 40.9075% at 30 minutes of irradiation for the Mn-N- TiO2/Bentonite composite and 20.0225% under exposure to ultraviolet light.